Severe Thrombocytopenia Two Weeks Following Immunization with the Janssen Ad26.CoV2.S Vaccine - Antonios, Bana; Zimmer, Markie; Herrman, Emma; Berghea, Ramona (Case Reports in Hematology, 2022)
Immune thrombocytopenia (ITP) has been associated with immunizations with various proposed mechanisms, including overactivation of the immune system and production of antibodies against circulating platelets. ITP has also been associated with several viral infections, including HCV, HIV, and most recently, active SARS-CoV-2 infection. Here, we present a case of a 52-year-old male with no past medical history who sought evaluation with his primary care physician for upper and lower extremity ecchymosis of one week duration. Outpatient laboratory studies were notable for severe isolated thrombocytopenia with platelet count of 8 × 10^9/L. Interestingly, he received the Johnson and Johnson COVID-19 vaccine 16 days prior to his presentation. Clinical work up and laboratory investigations led to the diagnosis of ITP.